2020
DOI: 10.46662/jass-vol7-iss2-2020(01-10)
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of English Vocabulary Learning Strategies Used by Iranian Bilinguals and Monolinguals

Abstract: The present study is an attempt to explore English vocabulary learning strategies employed by Iranian EFL undergraduate Baluch-Persian bilingual and Persian monolingual students in the University of Sistan and Baluchestan. The study utilized a between-groups research design. The participants of this study were 33 bilingual (Baluch-Persian) and 34 monolingual (Persian) students with an intermediate level of English. Their age ranged from 19 to 24 and. In order to collect the data, adapted version of Schmitt’s (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Language learning experience is directly related to language learning success, and it has been shown that as the number of languages learners know increases, they become better at learning additional languages (Brohy, 2001;Kemp, 2007). Similarly, the frequency with which learning strategies are employed by learners gradually increases as they learn additional languages (Sabeki & Karimzadeh, 2020;Yayla, Kozikoglu, & Celik, 2016). It is thus expected that there will be differences in bilinguals' and multilinguals' use of vocabulary learning strategies.…”
Section: Bilingualism and Multilingualismmentioning
confidence: 99%
“…Language learning experience is directly related to language learning success, and it has been shown that as the number of languages learners know increases, they become better at learning additional languages (Brohy, 2001;Kemp, 2007). Similarly, the frequency with which learning strategies are employed by learners gradually increases as they learn additional languages (Sabeki & Karimzadeh, 2020;Yayla, Kozikoglu, & Celik, 2016). It is thus expected that there will be differences in bilinguals' and multilinguals' use of vocabulary learning strategies.…”
Section: Bilingualism and Multilingualismmentioning
confidence: 99%